Pubertal Development among HIV-Infected Children aged 8-18 Years in Dar es Salaam, Tanzania: A Cross Sectional Study (Tanzania Medical Journal, 2021)
BackgroundPubertal development can be impaired among children living with HIV. This can lead to a psychosocial burden and subsequent negative self-image, social withdrawal and declining academic performance.Objective To assess timing of pubertal development of HIV infected children aged 8-18 years in Dar es Salaam, Tanzania.Methods This was a hospital-based cross-section study conducted at Amana and Mwananyamala, Care and Treatment Centres (CTC) in Dar es Salaam, Tanzania. A structured questionnaire was used to collect information on demographic and clinical characteristics. Participants were regarded to have entered puberty if they were at Tanner stage 2 or more for either breast (female) or genital (male) development and Tanner stage 2 or more for pubic hair development in both sexes. Data was analysed using STATA version 10 statistical packages. Puberty development of study participants was compared to their peers in a database of health children and adolescents attending schools in Dar es Salaam, Tanzania. Descriptive statistics were summarised as median (interquartile range), mean (standard deviation) for continuous variable and proportions for categorical variables. Differences in various groups was tested using Student t- test (means), Mann-Whitney U test (median) and chi square test (Proportions) and p value of < 0.05 was considered significant.ResultsA total of 330 HIV infected children were recruited, out of these 183 (55.4 %) were females. The median age of the study populations was 12.0 years (IQR 11-15). Median duration on ART at the time of the study was 48 months (IQR 30-62). Majority were in WHO stage III and had CD4 cell count above 500cells/µl. The median age at menarche for HIV infected adolescents was 15 years (IQR 14-16). HIV infected females and males had no significant age difference at baseline but attained puberty one or two years later than their HIV negative peers. Conclusion HIV infected children have delayed sexual maturation compared to their HIV negative peers. We recommend that as part of physical examination of an adolescent, sexual maturation to be emphasized and those identified to have delayed onset to be followed up and offered appropriate counselling.